Pharmacokinetics of cefquinome in rainbow trout (Oncorhynchus mykiss) after intravascular, intraperitoneal, and oral administrations - Durna Corum, Duygu; Corum, Orhan; Terzi, Ertugrul; Coskun, Devran; Bilen, Soner; Cetin, Gul; Uney, Kamil (Wiley, 2022)
AbstractThis study aimed to determine the pharmacokinetics and bioavailability of cefquinome in rainbow trout (Oncorhynchus mykiss) following intravascular (IV), intraperitoneal (IP), and oral (PO) administrations at 14 ± 1°C. In this study, three hundred and six clinically healthy rainbow trout (110–140 g) were used. The fish received single IV, IP, and PO injections of cefquinome at 10 mg/kg dose. The plasma concentrations of cefquinome were measured using HPLC‐UV and were evaluated using non‐compartmental analysis. Cefquinome was measured up to 96 h for PO route and 144 h for IV and IP routes in plasma. Following IV administration, t1/2ʎz, ClT, and Vdss were 18.85 h, 0.037 L/h/kg, and 0.84 L/kg, respectively. The Cmax of IP and PO routes was 9.75 and 1.64 μg/ml, respectively. The bioavailability following IP and PO administrations was 59.46% and 12.33%, respectively. Cefquinome at 10 mg/kg dose may maintain T > MIC above 40% at 72 and 96 h intervals, respectively, following the IP and IV routes for bacteria with MIC values of ≤2 μg/ml and at 24 h intervals following the PO route for bacteria with MIC value of ≤0.75 μg/ml. However, further studies are needed to determine in vitro and in vivo antibacterial efficacy and multiple dosage regimens of cefquinome against pathogens isolated from rainbow trout.
Keywords: Oncorhynchus mykiss; Animals; Administration, Oral; bioavailability; pharmacokinetics; rainbow trout; cefquinome; Cephalosporins; Anti-Bacterial Agents